Five feet apart [videorecording (DVD)] - Richardson, Haley Lu; Sprouse, Cole, 1992-; Forlani, Claire; Nagra, Parminder, 1975-; Arias, Moises, 1994- (Lionsgate, 2019)
Stella Grant is every bit a seventeen-year-old. She's attached to her laptop and loves her best friends. But unlike most teenagers, she spends much of her time living in a hospital as a cystic fibrosis patient. Her life is full of routines, boundaries and self-control, all of which is put to the test when she meets an impossibly charming fellow patient named Will Newman.